Efektifitas Akupresur Mengurangi Mual Muntah pada Ibu Hamil - Julaecha Julaecha; Ajeng Galuh Wuryandari (3031-8572, 2022)
Â Nausea, vomiting (emesis gravidarum) is a common complaint of 50-80% pregnant women, caused by changes in the endocrine system that occur during pregnancy. Nausea and vomiting causes a decrease in appetite and changes in electrolyte balance which affect changes in the body's metabolism, can develop into hyperemesis gravidarum and can affect the growth and development of the fetus. One of the non-pharmacological treatments is to reduce nausea and vomiting with acupressure/massage therapy at certain acupuncture points related to body organs/meridian points that can stimulate the regulatory system and activate endocrine and neurological mechanisms, which are physiological mechanisms in maintaining balance, so that nausea and vomiting are reduced. The purpose of this literature study is to determine the effectiveness of acupressure in treating nausea and vomiting in pregnant women. This literature study uses data sources based on the Google Scholar databases in the last 5 years, namely 2018-2022. Using the keyword acupressure, emesis gravidarum, the search results obtained 171 articles, but only 5 articles were reviewed according to the inclusion criteria determined by the authors. The results of the reviewed articles are the effectiveness of acupressure point pericardium 6 (PC 6/Nei Guan) in reducing nausea and vomiting in pregnant women. The conclusion of this literature review is that acupressure is an effective non-pharmacological therapy in reducing nausea and vomiting in pregnant women, easy to do, without the need for tools and patients can do it themselves, anytime, anywhere. It is hoped that health workers can provide information and education about acupressure as a non-pharmacological therapy for nausea and vomiting